Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.ajo.2015.06.006
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cataract Surgery on Patients With Wet Macular Degeneration

Abstract: Cataract surgery leads to vision improvement and does not appear to contribute to worsening of wet AMD. However, anatomic changes based on OCT analysis suggest a subclinical susceptibility to postoperative cystoid macular edema or exacerbation of choroidal neovascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 27 publications
5
24
1
Order By: Relevance
“…Apart from epidemiological cross-sectional studies, meta-analyses, and cohort studies, several smaller studies, similar to our randomized study in both the number of patients and study duration, have investigated the relationship between cataract surgery and AMD. Saraf et al performed a retrospective study of the effects of cataract surgery on BCVA, CRT, and the number of anti-VEGF injections in 2 groups of patients with wet AMD [ 39 ]. In total, 40 eyes underwent cataract surgery and the other 42 eyes did not.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from epidemiological cross-sectional studies, meta-analyses, and cohort studies, several smaller studies, similar to our randomized study in both the number of patients and study duration, have investigated the relationship between cataract surgery and AMD. Saraf et al performed a retrospective study of the effects of cataract surgery on BCVA, CRT, and the number of anti-VEGF injections in 2 groups of patients with wet AMD [ 39 ]. In total, 40 eyes underwent cataract surgery and the other 42 eyes did not.…”
Section: Discussionmentioning
confidence: 99%
“…They found that shorter delays of cataract surgery after diagnosis of wet AMD and shorter exudation-free periods before cataract surgery were associated with increased risk of recurrence. Thus, they suggested lower risk of recurrence for eyes with stabilized exudation more than 12 months; but, unfortunately this study did not compare with a control group (non-surgical group) [38].…”
Section: Neovascular Amdmentioning
confidence: 91%
“…It is known that neovascular AMD, can compromise in 90% of cases severely the vision (20/200 or worse) if left untreated [37], but with the advent of anti-vascular Endothelial Growth Factor (anti-VEGF) intravitreal injections as therapy in wet AMD has got stabilize (90%) or even improved vision (30%) in a large number of cases [38][39][40][41][42][43].…”
Section: Neovascular Amdmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies published about cataract surgery in patients with neovascular AMD are mainly retrospective, FAG was only performed as a diagnostic test and not on the follow-up; some of them without control group and with short periods of follow-up [15,16,[25][26][27][39][40][41][42][43][50][51][52][53][54][55]58]. In addition, the protocols used in the reported studies, were inhomogeneous (treat and extend, pro-re-nata and monthly injections), but none compared these protocols between them, or even between different anti-VEGF agents (bevacizumab, ranibizumab or aflibercept) [38,39,[41][42][43][52][53][54][55]. Then, it is required prospective research of causality and not only epidemiological studies, with long periods of follow-up to clarify studies published until now concerning this issue.…”
Section: Neovascular Amdmentioning
confidence: 99%